2015
DOI: 10.1097/scs.0000000000001857
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Eccrine Spiradenoma of the Face

Abstract: Malignant eccrine spiradenoma, or spiradenocarcinoma, is an exceedingly rare sweat-gland tumor, with only 102 reported cases. Low-grade carcinomas are especially rare with only a few cases reported. Because of the limited number of case reports, the biologic behavior of low-grade malignant eccrine spiradenoma is poorly understood and no evidence-based therapeutic approach is established. Here, the authors report a 29-year-old woman who presented with a history of left-sided facial lesions present since the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Reports of tumors consisting of a combination of different skin adnexal carcinomas (21), duplicate reports (11), and studies in which data concerning SCs could not be distinguished from other skin adnexal tumors (7) were excluded. One hundred twenty patients were presented in 71 case reports 3,[6][7][8][9][10][11][12] and 3 case series. 5,14,81 Each case report was analyzed for patient'sage, sex, and ethnicity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports of tumors consisting of a combination of different skin adnexal carcinomas (21), duplicate reports (11), and studies in which data concerning SCs could not be distinguished from other skin adnexal tumors (7) were excluded. One hundred twenty patients were presented in 71 case reports 3,[6][7][8][9][10][11][12] and 3 case series. 5,14,81 Each case report was analyzed for patient'sage, sex, and ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…However, in the recent literature a more favorable clinical course in cases with low-grade histomorphological features has been reported. [4][5][6] The eccrine spiradenoma is considered the primary skin lesion from which an SC evolves, but de novo appearances have been reported as well. [7][8][9] Accelerated growth of a long-standing lesion, pain, and ulceration are the most common symptoms that lead to referral.…”
Section: Introductionmentioning
confidence: 99%
“…Computed tomography was the preferred modality, used in 49.1% of these cases, followed by magnetic resonance imaging (MRI) (32.7%), X-ray (30.9%), bone scan (23.6%), ultrasound (20%), positron emission tomography (PET)/computed tomography (CT) (14.5%) and finally mammography (10.9%). [4][5][6][8][9][10][11][54][55][56][57][58][60][61][62][63][67][68][69][73][74][75][77][78][79] Staiger et al have recently recommended that patients presenting with confirmed malignant spiradenoma be evaluated with an MRI and fluorodeoxyglucose (FDG)-PET/CT. 74 Details regarding a fineneedle aspirate or punch biopsy was provided for 76 case reports and case series, representing 86 (61.9%) cases.…”
Section: Investigationsmentioning
confidence: 99%
“…This pre-operative test was performed 40.7% of the time, with the majority of surgeons electing to proceed firstly with excisional biopsy or wide local excision. [4][5][6][7][8][9][10][11][12][18][19][20][21][22][24][25][26][27][28][29][54][55][56][57][58][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][77][78][79][80][81][82][83][84][85][86][8...…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation